IDENTIFIKASI PERSEBARAN DAYA TARIK WISATA DI KAWASAN PARIWISATA UBUD KABUPATEN GIANYAR BALI - Ida Ayu Karina Putri (Universitas Triatma Mulya, 2023)
he Ubud Tourism Area is a prominent tourist destination located within the Gianyar Regency. The Ubud Tourism Area encompasses the geographical regions of Ubud District, Tegallalang District, and Payangan District. The present investigation employs a qualitative descriptive methodology and subsequent analysis. The utilized data comprises both qualitative and quantitative data. Qualitative data pertains to narrative descriptions of tourist attractions, while quantitative data pertains to numerical information such as the area and distance traveled to reach these attractions. The study utilized primary and secondary data as its sources of information. The methodology employed in this study involves the collection of data through the means of observation, interviews, and documentation. The present study elucidates the categorization of tourist attractions in the Ubud Tourism Area into three distinct types, namely natural, cultural, and artificial tourist attractions. The Ubud Tourism Area encompasses several natural tourist attractions, namely the Padang Tegal, Ceking, Ayung River, and Campuhan Hill Monkey Forests. The Ubud Tourism Area encompasses a range of cultural tourist attractions, such as Puri Saren Ubud, the Painting Museum, and the Arma Museum. Alas Harum Agrotourism is a man-made tourist destination located in the Ubud Tourism Area.